2000
DOI: 10.1086/308907
|View full text |Cite
|
Sign up to set email alerts
|

New Techniques for Relating Dynamically Close Galaxy Pairs to Merger and Accretion Rates: Application to the Second Southern Sky Redshift Survey

Abstract: The galaxy merger and accretion rates, and their evolution with time, provide important tests for models of galaxy formation and evolution. Close pairs of galaxies are the best available means of measuring redshift evolution in these quantities. In this study, we introduce two new pair statistics, which relate close pairs to the merger and accretion rates. We demonstrate the importance of correcting these (and other) pair statistics for selection e †ects related to sample depth and completeness. In particular,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
408
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 238 publications
(429 citation statements)
references
References 34 publications
20
408
1
Order By: Relevance
“…Following Patton et al (2000Patton et al ( , 2002 and our previous work, the number of close companions per galaxy is:…”
Section: Dataset and Methodologymentioning
confidence: 99%
See 2 more Smart Citations
“…Following Patton et al (2000Patton et al ( , 2002 and our previous work, the number of close companions per galaxy is:…”
Section: Dataset and Methodologymentioning
confidence: 99%
“…The second weight is for galaxies close (within 500 km s −1 ) to the redshift limits of each volume-limited box, and accounts for possible companions missed because they lie just beyond these boundaries. As in Patton et al (2000Patton et al ( , 2002) the value of this weight is set at 2. Similar weights need to be applied to the primary sample as well, to account for missed primaries in the same manner (recall that both primary and secondary samples are the same):…”
Section: Dataset and Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…Owers et al 2012), while galaxy merger or interaction rates can be studied using analysis of galaxy close pairs (e.g. Patton et al 2000;Robotham et al 2014). …”
Section: Environment Densitymentioning
confidence: 99%
“…Those authors recognise however that this cutoff requires a trade-off between contamination and completeness, with genuine pairs observed out to ∆v ∼ 600 km s −1 separations (Ellison et al 2008;Patton et al 2000). Ellison et al (2008) identified an enhancement in star formation rate for pairs with projected separations < 30 − 40 kpc, a criterion easily satisifed by the companion in this case (16 ′′ represents ∼ 27 kpc at this redshift), suggesting that the star formation observed in both host and companion is likely influenced by their proximity.…”
Section: Wht Spectroscopymentioning
confidence: 99%